The COVID-19 impact on crowdfunding performance: Evidence from a peer to-peer lending platform - Gama, A. P. M. (2023)
The COVID-19 impact on global poverty dragged another 97 million people into poverty in 2020. Nonetheless, there is scant evidence reporting on the impacts on alternative means of financing designed to enable the poor during this global health crisis. This paper addresses this gap of funding impoverished entrepreneurs by studying the changes in their successfully funded campaigns on the largest crowdfunding microfinance platform prior and during COVID-19. After collecting data from January 2018 to November 2021 for a total of 767,112 campaigns, we report that the COVID-19 pandemic positively impacts on the funding success of the crowdfunding campaigns. However, rises in the daily number of COVID-19 cases negatively associate with campaigns getting fully funded. The odds of campaigns being fully funded decrease by 4.4% for a one thousand increase in new cases.